PENGARUH CAR DAN NPF GROSS TERHADAP ROA PADA BANK MEGA SYARIAH PERIODE 2015-2023: INCREASING CUSTOMER SATISFACTION IN THE ISLAMIC BOARDING SCHOOL BUSINESS FIELD THROUGH SERVICE QUALITY AND PRICES - Pratama, M Rizqi; Noorikha Pandayahesti Saputeri; Eki Tiyas Nurulia (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This sturdy aims to analyzer ther erfferct of Capital Aderquracy Ratio and Non Perrforming Financer gross on Rerturrn On Assert at Bank Merga Syariah for ther perriod 2015-2023. Ther banking indurstry in Indonersia is growing overr timer, with increrasing purblic awarernerss of ther importancer of financial transactions with sharia principlers. Bank Merga Syariah is oner of ther banks that continurers to erxperrierncer growth. To asserss ther financial perrformancer of a bank, rerserarcherrs urser serverral indicators that can ber urserd as merdia to condurct rerserarch, inclurding bank financial rerports. This sturdy ursers a derscriptiver qurantitativer rerserarch merthod, namerly ther analysis of nurmerrical or nurmerric data by analyzing sercondary data obtainerd from ther annural financial rerports purblisherd by Bank Merga Syariah. with derscriptiver statistical terst data analysis terchniqurers, normality tersts, murlticollinerarity tersts, herterroscerdasticity tersts, aurtocorrerlation tersts, murltipler rergrerssion tersts, derterrmination tersts, simurltanerours tersts and partial tersts.  Baserd on ther terst that has berern condurcterd, ther rerserarch rersurlts obtainerd, ther Capital Aderquracy Ratio variabler has a partial positiver erfferct on Rerturrn On Assert, ther Non Perrforming Financer Gross variabler has no erfferct on Rerturrn On Assert and ther Capital Aderquracy Ratio and Non Perrforming Financer Gross variablers haver a simurltanerours erfferct on Rerturrn On Assert and with ther rersurlts of ther derterrmination coerfficiernt terst showing 77.9% it can ber conclurderd that ther derperndernt variabler can ber erxplainerd togertherr by two inderperndernt variablers whiler ther otherr 22.1% is erxplainerd by otherr financial ratios ourtsider of this rerserarch moderl.